2013
DOI: 10.18832/kp2013030
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the occurrence of deoxynivalenol in beers from outlet shops in 2009-2012.

Abstract: Klíčová slova: pivo, mykotoxiny, deoxynivalenol, LC/MS■ ■ 1 ÚVOD Pivo je slabě alkoholický nápoj, který se po staletí vyrábí z obilných sladů, vody a chmele za účasti pivovarských kvasinek . Ječmen setý je základní surovinou pro výrobu sladu v tradičních pivovarských zemích . Tato starobylá rostlina prošla při domestikaci vývo-jem od převážně potravinářského obilí po krmivo a sladovnické obilí (Basařová et al ., 2010;Hegrova et al ., 2009) . Složení mikroflóry zrna ječmene je ovlivňováno zejména geografickými … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…The transfer of myxotoxins from crops to food products (plant-based and animal food source) is also studied. Běláková et al (2013) analysed the occurrence of DON in beers available on the market and found that common levels of mycotoxins in brewing raw materials and in beer did not represent any significant health risk. Štočková and Chrpová (2012) Spring barley is one of the staple crops; in the Czech Republic it is important mainly for malt production.…”
Section: ■ ■ 3 Výsledky a Diskusementioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of myxotoxins from crops to food products (plant-based and animal food source) is also studied. Běláková et al (2013) analysed the occurrence of DON in beers available on the market and found that common levels of mycotoxins in brewing raw materials and in beer did not represent any significant health risk. Štočková and Chrpová (2012) Spring barley is one of the staple crops; in the Czech Republic it is important mainly for malt production.…”
Section: ■ ■ 3 Výsledky a Diskusementioning
confidence: 99%
“…Pozornost je věnována také možnému přechodu mykotoxinů do potravin rostlinného původu i do živočišných produktů jako následek zkrmování kontaminovaného obilí. Běláková et al (2013) Obsah mykotoxinů DON a NIV v zrnu byl stanoven akreditovanou referenční analytickou metodou -vysokoúčinnou kapalinovou chromatografií spojenou s tandemovou hmotnostní spektrometrií (HPLC-MS/MS) na Ústavu analýzy potravin a výživy VŠCHT Praha (Vaclavikova et al, 2013;Cajka et al, 2014a Dzuman et al, 2014b.…”
Section: ■ 1 Introductionunclassified